Aplastic anemia presenting as hemophagocytic lymphohistiocytosis - Tiraje Celkan (Turkish Journal of Hematology, 2010)
Two unusual cases of hemophagocytic lymphohistiocytosis (HLH) complicating aplastic anemia (AA) are described. Each patient had a history of preexisting acute hepatitis of unknown cause at the time of HLH diagnosis and infection-associated secondary HLH. They developed high fever and pancytopenia. Hemophagocytes were seen in the bone marrow. With steroid (in combination with etoposide and CyA in 1 patient), high fever disappeared and the patients’ liver function gradually recovered. As severe pancytopenia persisted, bone marrow became acellular and AA was diagnosed. Since HLH is known to be able to cause an aplastic bone marrow if untreated for a prolonged time, it is therefore in line that hepatitis-associated AA may also be associated with HLH. Aplastic anemia-associated HLH has been reported rarely, and problems in the diagnostic procedure are discussed.